Comparative evaluation of the quality of life of patients depending of different inframammary fold creation techniques during a two-stage breast reconstruction - A. Kh. Ismagilov; I. F. Kamaletdinov (Опухоли женской репродуктивной системы)
Reconstruction of natural-looking breast involves the restoration of all the constituent elements that define the identity of a normal breast. The inframammary fold is one of the main anatomical elements that determine the shape of the breast. That is why the technical features of various methods of the inframammary fold reconstruction affect the final aesthetic result of the reconstructive surgery. This article considers a comparative evaluation of the quality of life and satisfaction with the reconstructed breast after the two-stage breast reconstruction with different inframammary fold creation techniques.